2019
DOI: 10.3889/oamjms.2019.652
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Training Course on Accuracy of Triaging of Pediatric Patients

Abstract: BACKGROUND:In the context of a new but busy Pediatric Emergency Department, the risk of missing patients who need more emergent care can be reduced by timely and accurate triaging. In the emergency department of King Fahad Armed Forces Hospital, the Canadian Triage and Acuity Scale had already been implemented, including the pediatric version (PaedCTAS). However, a common observation remained that critical patients did not always receive priority with subsequent delays in management. To improve this accuracy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Recently, in a study based on 15 pediatric scenarios, Alshaibi 18 showed a mistriage rate of more than 50% among nurses using CTAS. Using the CTAS on more than 31,000 pediatric patients, Azzam et al 19 showed an accuracy of approximately 57% before training, with an improvement to 78% after training. Finally, a Swedish team reported a correct triage rate of 57.6% based on 7614 triage decisions with the CTAS (423 nurses and 18 scenarios).…”
Section: °Accuracymentioning
confidence: 99%
“…Recently, in a study based on 15 pediatric scenarios, Alshaibi 18 showed a mistriage rate of more than 50% among nurses using CTAS. Using the CTAS on more than 31,000 pediatric patients, Azzam et al 19 showed an accuracy of approximately 57% before training, with an improvement to 78% after training. Finally, a Swedish team reported a correct triage rate of 57.6% based on 7614 triage decisions with the CTAS (423 nurses and 18 scenarios).…”
Section: °Accuracymentioning
confidence: 99%